NANOTECHNOLOGY ADVANCEMENTS: FROM MATERIALS SCIENCE TO MEDICINE (American Journal of Technology and Applied Sciences, 2023)
This scientific article provides a comprehensive analysis of nanotechnology advancements in various fields, with a specific focus on materials science and medicine. The article highlights key breakthroughs, explores the potential applications of nanotechnology, and discusses the implications for future research and development. The analysis is divided into sections including annotation, keywords, introduction, literature analysis and methodology, results, discussion, conclusion, and a list of references.